Perkembangan Hubungan Antarsektor dan Antar Daerah dalam Perekonomian Indonesia: Analisa Model Interregional Input-Output Tahun 1995 dan 2000 - Hirawan, Susiati B.; Nurkholis, Nurkholis (UI Scholars Hub, 2007)
The changes in sectors and linkages in Indonesian economy have been changing thus affecting the structure. This study aims to evaluate the changes in the nation's economic structure by focusing 011 the development of intra/inter sectors and intra/inter regions linkage using Interregional Input-Output (IRIO) model in 1995 and 2000 data. The model analyzes the changes by applying the concept of technical coefficient stability, testing changes on the coefficients, and exploring the basic IRIO model. The study found that there has been a significant decrease of relative relationship between sectors and regions in Indonesian economy albeit of seemingly in significant. Further, the analysis in intra and inter regions showed that an increase in intra regions relationship has not been significant meanwhile the decrease of inter regions relationship has been significant. The studies also revealed that industry was a high potential sector in national development priorities not only because of its high multiplier but also its role in strengthening and increasing the interactions of intra/inter sectors and intra/inter regions.